MHC-Based Mate Choice in Wild Golden Snub-Nosed Monkeys - Zhang, Bing-yi; Hu, Han-yu; Song, Chun-mei; Huang, Kang; Dunn, Derek W.; Yang, Xi; Wang, Xiao-wei; Zhao, Hai-tao; Wang, Cheng-liang; Zhang, Pei; Li, Bao-guo (Frontiers in Genetics, 2020)
The genes of the major histocompatibility complex (MHC) are an important component of the vertebrate immune system and play a significant role in mate choice in many species. However, it remains unclear whether female mate choice in non-human primates is based on specific functional genes and/or genome-wide genes. The golden snub-nosed monkey (Rhinopithecus roxellana) lives in a multilevel society, which consists of several polygynous one-male-several-female units. Although adult females tend to mainly socialize with one adult male, females often initiate extra-pair copulations with other males resulting in a high proportion of offspring being fathered by extra-pair males. We investigated the effects of adaptive MHC genes and neutral microsatellites on female mate choice in a wild R. roxellana population. We sequenced 54 parent-offspring triads using two MHC class II loci (Rhro-DQA1 and Rhro-DQB1) and 20 microsatellites from 3-year of data. We found that the paternities of offspring were non-randomly associated with male MHC compositions not microsatellite genotypes. Our study showed that the fathers of all infants had significantly less variance for several estimates of genetic similarity to the mothers compared with random males at both MHC loci. Additionally, the MHC diversity of these fathers was significantly higher than random males. We also found support for choice based on specific alleles; compared with random males, Rhro-DQA1* 05 and Rhro-DQB1* 08 were more common in both the OMU males and the genetic fathers of offspring. This study provides new evidence for female mate choice for MHC-intermediate dissimilarity (rather than maximal MHC dissimilarity) and highlights the importance of incorporating multiple MHC loci and social structure into studies of MHC-based mate choice in non-human primates.